PENGARUH PROBLEM-BASED LEARNING DENGAN STRATEGI TAPPS TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PADA MATERI PERBANDINGAN - Nurwulan, Intan; Irawati, Riana; Subarjah, Herman (Jurnal Pena Ilmiah, 2017)
This study was conducted to determine the increase in mathematical problem solving ability of students with mathematics learning using the Problem-Based Learning with TAPPS strategy on 5th grader comparative material. This research method using a quasi-experimental method by nonequivalent control group design. Samples were selected in the study were students of SDN Sukaraja II 5th grader. There are various instruments used in the study, such as tests the ability of mathematical problem solving, observation formats, and the format of student questionnaire responses. Research results with a significance level (Î±) = 0.05 indicates that learning using the Problem-Based Learning with TAPPS strategy and conventional learning can enhance students' mathematical problem solving ability. Problem-Based Learning with TAPPS strategy significantly better than conventional learning in improving mathematical problem solving ability. Students' response to mathematics learning using Problem-Based Learning with TAPPS strategies that have been implemented relatively positive.